Трансформація суспільної свідомості як довгострокова причина революції - Ідрісов, Бахтійор; Idrisov, Bahtiyar; Идрисов, Бахтиѐр (Східноєвропейський національний університет імені Лесі Українки, 2019)
Вивчення питань революції становлять безсумнівний науковий інтерес у контексті зміни суспільної свідомості і її впливу на швидкість соціальних процесів. Проведений порівняльний аналіз зарубіжних і вітчизняних соціологічних досліджень засвідчив, що наукові пояснення виникнення й розвитку революції відрізняються достатньою варіативністю. У дослідженні подано класифікацію найбільш визнаних теорій революції, складену за схожими причинами їх виникнення. Особливу увагу приділено біхеоверистським концепціям, у яких вивчаються питання масової психології й виокремлено умови зміни суспільної свідомості. Доведено, що основною причиною українських революцій є збереження революційної ситуації, викликаної періодичною трансформацією суспільної свідомості. Визначено, що періоди трансформації являють собою повторюваний взаємозв’язок ланок-фаз: «соціальна дезорієнтація – соціальна аномія – соціальний цинізм – соціальне безумство», – які характеризуються звуженням у часі. The study of revolution issues is of undoubted scientific interest in the context of changes in social consciousness and its influence on the speed of social processes. A comparative analysis of foreign and domestic sociological studies has shown that scientific explanations for the emergence and development of a revolution are quite variable, which is due to the personal vision of scientists in identifying factors and ranking the main causes. And, accordingly, depending on the ultimate goal of the research, the meaning of the concept itself acquires a negative or positive meaning. Therefore, in the course of work on this article, we presented a classification of the most recognized theories of revolution, compiled for similar reasons for their occurrence, and grouping was carried out according to similar signs and methods of study. Particular attention is paid to behavioral concepts in which questions of mass psychology are studied, and, accordingly, a set goal, we have highlighted the conditions for a change in social consciousness. The study proved that the main cause of Ukrainian revolutions is the preservation of the revolutionary situation caused by the periodic transformation of the public consciousness. Periods of transformation are a recurring interrelation of links-phases: «social disorientation – social anomie – social cynicism – social madness», each of which is a logical consequence and a continuation of the previous one, and is characterized by a narrowing in time. It should be noted that the article considers only the psychological aspect of the causes of revolutions – for a more detailed analysis it is necessary to consider such factors as the development of the state, which depends on the external conjuncture, the economic, political, military and cultural components.
Transformation of Social Consciousness as a Long-Term Cause of the Revolution
Трансформация общественного сознания как долгосрочная причина революции
Keywords: радикальні соціальні процеси; революційна ситуація; соціальна аномія; radical social processes; revolutionary situation; social anomy